The Relationship of Satisfaction and Usage of Virtual Learning Facilities with Learning Style in Medical, Health, and Operating Room Students - Daryosh Gholipour Mofrad Dashtaki; Aeen Mohammadi; Mitra Zolfaghari; Sakineh Imani; Shahram Tahmasebian (Kerman University of Medical Sciences, 2020)
Background: Nowadays, several studies have been performed on the factors affecting the effectiveness of virtual education. One of the characteristics of learners is their different learning styles.Objectives: The purpose of this study was to investigate the relationship between learning style and the level of satisfaction and usage of e-learning facilities in medical students.Methods: This cross-sectional and retrospective (ex post facto) study was performed among medical, public health, and operating room students of Shahrekord University of Medical Sciences in 2017. We redesigned their courses to be delivered in the blended method, so that teachers used a Learning Management System (LMS) in addition to traditional teaching. Information about learning styles was collected using Kolb's questionnaire, satisfaction level evaluated with a researcher made questionnaire and use of e-learning was examined by checking system loggings. Data were analyzed using one-way ANOVA, Tukey's post hoc, Welch's ANOVA and X2 tests in SPSS software.Results: Students' satisfaction with e-content in diverging learning style was higher (P = 0.032), but there was no significant relationship between learning style and demographic characteristics and total average mark. Also, there was no significant difference in the amount of using e-learning facilities between different learning style groups (P = 0.256).Conclusion: It seems that using virtual learning facilities and considering the type of learning style in students can increase their satisfaction.